COVID-19 Outbreak and BNT162b2 mRNA Vaccination Coverage in a Correctional Facility during Circulation of the SARS-CoV-2 Omicron BA.1 Variant in Italy - Stufano, Angela; Buonvino, Nicola; Trombetta, Claudia Maria; Pontrelli, Daniela; Marchi, Serena; Lobefaro, Giuseppe; De Benedictis, Leonarda; Lorusso, Eleonora; Carofiglio, Maria Teresa; Vasinioti, Violetta Iris; Montomoli, Emanuele; Decaro, Nicola; et al. (Vaccines (Basel), 2022)
Background. The recent spread of the highly mutated SARS-CoV-2 Omicron variant (B.1.1.529) has raised concerns about protection against COVID-19 in congregate settings such as prisons, characterized by a high risk of transmission and possible difficulties in obtaining adequate vaccination coverage. The present study aims to investigate the spread of an outbreak of COVID-19 in an Italian correctional facility during the dominant circulation of the Omicron BA.1 variant, and also considers BNT162b2 mRNA vaccination coverage among inmates. A COVID-19 screening campaign by RT-PCR was performed on 515 detainees from 4–30 January 2022, in response to an outbreak that began in the correctional facility. Furthermore, 101 serum samples collected from healthy inmates 21 days after having received the second dose of the BNT162b2 vaccine were tested for neutralizing antibodies against both the wild-type SARS-CoV-2 strain and the Omicron BA.1 variant. The global attack rate during the study period was 43.6% (RR 0.8), progressively reducing from unvaccinated inmates (62.7%, RR 1.8) to those who had one dose (52.3%, RR 1.5), two doses (full cycle) (45.0%, RR 1.3), and the third dose (booster) vaccinated group (31.4%, RR 0.7). The percentage of SARS-CoV-2 positive subjects among unvaccinated inmates was significantly higher than in the other groups (p < 0.001), while no significant difference was observed between inmates with one or two vaccine doses. Only two of the positive inmates were hospitalized for COVID-19. The geometric mean titer of neutralizing antibodies in the tested sub-group after two doses of vaccine was lower than in previous studies against the wild-type virus, and showed a complete lack of neutralization against the Omicron variant in 92.1% of individuals. The findings support the need to prioritize vaccination in correctional facilities, as a public health measure to increase the protection of inmates and consequently of prison workers and the community against COVID-19, in coordination with the other prevention strategies.